Experimental investigation of banana bract fiber and palm fiber reinforced with epoxy hybrid composites. (2020) - Dinesh, S.; Elanchezhian, C.; Vijayaramnath, B.; Sathiyanarayanan, K.; Adinarayanan, A.
Abstract: This investigation is carried out by making a new hybrid natural composite material used Kevlar fabrics, Banana bract fibers and palm fibers. In this research, the samples prepared by hand lay method and tested for its Tensile behaviors. The fractured surfaces are analyzed by Scanning Electron Microscope (SEM). The leakages and quality of the specimen are checked by Water Absorption test. As a result, the banana bract and Kevlar composite sample shows optimum tensile strength compared to other samples and less water absorption which is useful in the application of Marine Engineering.